1991
DOI: 10.1037/0022-006x.59.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral, cognitive, and pharmacological treatments of panic disorder with agoraphobia: Critique and synthesis.

Abstract: Theoretical, methodologic, and clinical research issues pertaining to these treatments are examined as are their strengths, limitations, and possible interactions. Attrition, outcome, and maintenance effects are compared. Composite indices of clinically significant improvement, endstate functioning, and longitudinal adjustment are presented. The article also highlights emerging models, theoretical advances, and promising interventions. Advantages and limitations of current treatments are discussed, with recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
15

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 77 publications
0
47
0
15
Order By: Relevance
“…The efficacy of cognitive behavior therapy in the treatment of panic disorder is well established (33,(41)(42)(43)(44). In a recent review of 12 clinical trials, the mean panic-free rate after cognitive behavior therapy among intent-to-treat subjects was 77% (41).…”
Section: Cognitive Behavior Therapymentioning
confidence: 99%
“…The efficacy of cognitive behavior therapy in the treatment of panic disorder is well established (33,(41)(42)(43)(44). In a recent review of 12 clinical trials, the mean panic-free rate after cognitive behavior therapy among intent-to-treat subjects was 77% (41).…”
Section: Cognitive Behavior Therapymentioning
confidence: 99%
“…Volgens het relevantie criterium kon een kwart van de patiënten min of meer klachtenvrij worden ontslagen. Dropouts werden hierbij uit de berekeningen weggelaten (Jacobson et al, 1988 Overigens is men vrij algemeen van mening dat alleen EV meestal niet voldoende is om agorafobie te genezen (Marks, 1987a;Michelson & Marchione, 1991). Toch achten ook critici van het exposure-model de interventie redelijk effectief bij de behandeling van agorafobici.…”
Section: Effecten Van De Behandeling Van Agorafobie Met Evunclassified
“…Of men cognitieve therapie effectief acht in de behandeling van paniek (Barlow, 1988;Teasdale, 1988) of niet hangt deels af van wat men onder cognitieve therapie verstaat (Michelson & Marchione, 1991). Soms noemt men een training in het genereren van positieve zelfverbalisaties cognitieve therapie (Emmelkamp & Mersch, 1982), dan weer noemt men de modificatie van 'core-beliefs' cognitieve therapie (vgl.…”
Section: Effecten Van De Behandeling Van Paniekunclassified
“…When planning the treatment project, from which the present data comes, no randomized controlled treatment trials that explicitly assessed the potential beneficial effects of adding cognitive therapy for panic attacks to exposure in vivo were available. In spite of the stated potential promise of these methods, this applied to this population (e.g., Michelson & Marchione, 1991).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Only one study has found more substantial beneficial effects (Michelson et al, 1996), and one study (Williams & Falbo, 1996) showed inferior results in the cognitive condition. This failure should also be considered in the light of high expectations for this approach (e.g., Michelson & Marchione, 1991) and the possibility of allegiance effects.…”
Section: Treatment Efficacymentioning
confidence: 99%